4(2x-1)=9

Simple and best practice solution for 4(2x-1)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-1)=9 equation:


Simplifying
4(2x + -1) = 9

Reorder the terms:
4(-1 + 2x) = 9
(-1 * 4 + 2x * 4) = 9
(-4 + 8x) = 9

Solving
-4 + 8x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 8x = 9 + 4

Combine like terms: -4 + 4 = 0
0 + 8x = 9 + 4
8x = 9 + 4

Combine like terms: 9 + 4 = 13
8x = 13

Divide each side by '8'.
x = 1.625

Simplifying
x = 1.625

See similar equations:

| =x^2-8x+63 | | 3-5b=7-3b | | .4x+8.5=.65(x+10) | | =x^2-8x+67 | | y+6=-4(x+4) | | =x^2-10x+98 | | 9-x=12-5x | | 5x^2+30-60=0 | | 5x^2+1-246=0 | | 5(x+y)=zforx | | 9-c=12-5c | | f(x)=x^2-10x+98 | | 5x^2+26-24=0 | | Y=8/9x-4 | | 9x-1=107 | | x^3+3x-2=0 | | 7[4-(3-5x)]+x=4(9x+2)-1 | | -10x+3(x-4)+6x=5x-48 | | 2-6=36x-5 | | x-2+x+3=3x-4 | | x(5x+7)=2x^2-9x+64 | | 15x-60=-12x-54 | | -[4z-(9z+8)]=8+(4z+6) | | 3x^9/2x^5 | | 10+6r=104 | | 8a-2a+12=10a-4 | | 10-6r=104 | | 10a-22=13a+5 | | 15=6-2a | | 7+1=7x-11 | | 4a+18=2a-26 | | 1=(x+1)ln(x+1)+xln(x) |

Equations solver categories